Human papillomavirus prevalence and type distribution in invasive cervical cancer in sub‐Saharan Africa. Issue 6 (14th November 2013) - Denny, Lynette; Adewole, Isaac; Anorlu, Rose; Dreyer, Greta; Moodley, Manivasan; Smith, Trudy; Snyman, Leon; Wiredu, Edwin; Molijn, Anco; Quint, Wim; Ramakrishnan, Gunasekaran; Schmidt, Johannes
<x xml:space="preserve">Abstract</x> In sub‐Saharan Africa, invasive cervical cancer (ICC) incidence and mortality are among the highest in the world. This cross‐sectional epidemiological study assessed human papillomavirus (HPV) prevalence and type distribution in women with ICC in Ghana, Nigeria, and South Africa. Cervical biopsy specimens were obtained from women aged ≥21 years with lesions clinically suggestive of ICC. Histopathological diagnosis of ICC was determined by light microscopy examination of hematoxylin and eosin stained sections of paraffin‐embedded cervical specimens; samples with a confirmed histopathological diagnosis underwent HPV DNA testing by polymerase chain reaction. HPV‐positive specimens were typed by reverse hybridization line probe assay. Between October 2007 and March 2010, cervical specimens from 659 women were collected (167 in Ghana, 192 in Nigeria and 300 in South Africa); 570 cases were histologically confirmed as ICC. The tumor type was identified in 551/570 women with ICC; squamous cell carcinoma was observed in 476/570 (83.5%) cases. The HPV‐positivity rate in ICC cases was 90.4% (515/570). In ICC cases with single HPV infection (447/515 [86.8%]), the most commonly detected HPV types were HPV16 (51.2%), HPV18 (17.2%), HPV35 (8.7%), HPV45 (7.4%), HPV33 (4.0%) and HPV52 (2.2%). The prevalence of single and multiple HPV infections seemed higher among HIV‐positive women and HPV type distribution appeared to differ according to tumor type and HIV status. In conclusion, HPV16, 18, 45 and 35 were the most common HPV types in sub‐Saharan African women with ICC and HPV infections were more common in HIV‐positive women.